Efforts to Improve Students' Gender Equality Attitude through Social Inclusion Gender Learning in Grade V Elementary School (Universitas Negeri Semarang, 2022)
Education in Indonesia itself has implemented character education programs for all students. Character education is a program of learning activities in schools so that students experience changes in student attitudes to become better. The application of good character education can be done by enforcing gender learning and eliminating differences in each student. The research method used is a combination of qualitative and quantitative descriptive models. The subjects used in this study were the principal of the elementary school and the fifth grade teacher of the elementary school. Qualitative data collection techniques used in this study in the form of interviews, documentation and field notes. Quantitative data collection techniques in this study are in the form of taking grades V elementary school students through assessment through observation. The result of this study is that the school seeks to improve students' attitude skills by applying gender equality between male and female students without any difference and the results of the assessment carried out are that male students' attitudes are superior to female students with a very good category.